Influencing Factors and Prediction Model for the Antierosion Performance of Cement-Improved Loess Compacted Using Different Compaction Methods. (6th August 2021) - Yuan, Kejia; Jiang, Yingjun; Cai, Luyao; Fan, Jiangtao; Deng, Changqing; Xue, Jinshun
Abstract : To analyze the antierosion performance of cement-improved loess (CIL), several influencing factors have been investigated based on two different compaction methods, which include the quasi-static compaction method (QSCM) and the vertical vibration compaction method (VVCM). Then, a prediction model for the cumulative erosion mass loss (CEML) has been established. The effects of erosion on the strength deterioration of CIL were also studied. The results show that, compared with QSCM, specimens compacted using the VVCM have better antierosion performance. As the cement content and the compaction coefficient are increased by 1%, the antierosion performance is increased by 16% and 6.2%, respectively. The eroding time has a significant effect on the antierosion performance of CIL, and the CEML increases linearly with an increase in the eroding time. The compressive strength of CIL decreases significantly due to erosion, and based on the average deterioration degree of the specimens, the design criteria for strength of CIL are proposed, which can provide reference for the design of CIL.